(3QbGFb GdMbGFb aj MSGH GdOQL hGdObGFbs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3djS ai MSGH GdCYeGd GdadcjI CMSf ef WQjb MSGH GdfSHI GdSJjfjg hgj GdeSJYedg ai YUQfG gPG s
(3BNQgG (B:s
(3bHd MeO Gddg (B: (3hGdBf ced dfG ef Gddg JYGdi hYhfg heG CQOfG hVYg ai gPg GdebOeI hJCSSJ bhGYOg , hhVYJ eTcdGJg hJgPjH CHhGHg hJaJMJ WQbg hJMQQJ CeKdJg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B168 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B59 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI ShgGL (B((3adc (B28) s
Keywords: (3Gdadcs